Outcome following preterm intraventricular haemorrhage – what to tell the parents. Issue 9 (September 2018) - Jones, Rebekka Manuela; Clark, Emily Michelle; Broad, Katherine; Smit, Elisa
Abstract: Despite advances in neonatal care and overall improved survival rates of preterm infants, intraventricular haemorrhage (IVH) remains an important cause of mortality and long-term neurodevelopmental morbidity in the preterm population. Counselling parents regarding possible outcomes following IVH can be very challenging, particularly as prognostication can be difficult in the early stages. This article gives an overview of the incidence, pathophysiology, clinical manifestations, treatment and classification of IVH. In addition, it reviews the currently available outcome data following IVH including recent publications on less severe IVH previously not thought to be of particular clinical significance. It includes best practice recommendations for parental discussions and decision-making.